Mortality comparison between the first and second/third waves among 3,795 critical COVID-19 patients with pneumonia admitted to the ICU: A multicentre retrospective cohort study - Raquel Carbonell (Elsevier, 2021)
ABSTRACT: Background: It is unclear whether the changes in critical care throughout the pandemic have improved the outcomes in coronavirus disease 2019 (COVID-19) patients admitted to the intensive care units (ICUs). Methods: We conducted a retrospective cohort study in adults with COVID-19 pneumonia admitted to 73 ICUs from Spain, Andorra and Ireland between February 2020 and March 2021. The first wave corresponded with the period from February 2020 to June 2020, whereas the second/third waves occurred from July 2020 to March 2021. The primary outcome was ICU mortality between study periods. Mortality predictors and differences in mortality between COVID-19 waves were identified using logistic regression. Findings: As of March 2021, the participating ICUs had included 3795 COVID-19 pneumonia patients, 2479 (65·3%) and 1316 (34·7%) belonging to the first and second/third waves, respectively. Illness severity scores predicting mortality were lower in the second/third waves compared with the first wave according with the Acute Physiology and Chronic Health Evaluation system (median APACHE II score 12 [IQR 9–16] vs 14 [IQR 10–19]) and the organ failure assessment score (median SOFA 4 [3–6] vs 5 [3–7], p<0·001). The need of invasive mechanical ventilation was high (76·1%) during the whole study period. However, a significant increase in the use of high flow nasal cannula (48·7% vs 18·2%, p<0·001) was found in the second/third waves compared with the first surge. Significant changes on treatments prescribed were also observed, highlighting the remarkable increase on the use of corticosteroids to up to 95.9% in the second/third waves. A significant reduction on the use of tocilizumab was found during the study (first wave 28·9% vs second/third waves 6·2%, p<0·001), and a negligible administration of lopinavir/ritonavir, hydroxychloroquine, and interferon during the second/third waves compared with the first wave. Overall ICU mortality was 30·7% (n = 1166), without significant differences between study periods (first wave 31·7% vs second/third waves 28·8%, p = 0·06). No significant differences were found in ICU mortality between waves according to age subsets except for the subgroup of 61–75 years of age, in whom a reduced unadjusted ICU mortality was observed in the second/third waves (first 38·7% vs second/third 34·0%, p = 0·048). Non-survivors were older, with higher severity of the disease, had more comorbidities, and developed more complications. After adjusting for confounding factors through a multivariable analysis, no significant association was found between the COVID-19 waves and mortality (OR 0·81, 95% CI 0·64–1·03; p = 0·09). Ventilator-associated pneumonia rate increased significantly during the second/third waves and it was independently associated with ICU mortality (OR 1·48, 95% CI 1·19–1·85, p<0·001). Nevertheless, a significant reduction both in the ICU and hospital length of stay in survivors was observed during the second/third waves. Interpretation: Despite substantial changes on supportive care and management, we did not find significant improvement on case-fatality rates among critical COVID-19 pneumonia patients. Funding: Ricardo Barri Casanovas Foundation (RBCF2020) and SEMICYUC.